Sucessão, profissionalização e governança: um estudo multicasos em empresas familiares mineiras - Rafael Diogo Pereira (2010)
The social and economical relevance of family-owned businesses, both nationally and internationally, constitutes a vastly referenced topic in this fields literature. The central proposal of this dissertation consists in identifying and analyzing succession and professionalization processes in family owned-businesses in the state of Minas Gerais. Also, it is sought to understand the role that governance and the degree of formalization in the researched companies have. In the field of organizational studies, the succession and professionalization processes of family-owned businesses are often and commonly discussed; however, very few approach the issue of implementation of these processes together with the governance structuring. The themeitself (governance in the family owned business) reveals few papers and work in the field of organizational studies. The theoretical basis used was structured around a broad revision of the themes Family Owned Businesses and Corporate Governance. In regards to the methodological aspects, this study is based on qualitative research strategy, adopting the multicase study method. Content Analysis was used as the analysis technique, and the software N-Vivo®QSR (version 7.0) was used for the data treatment. The locus of the research corresponds to three companies from Minas Gerais inside the textile, transportation and coffee agriculture businesses. The corpus of the study consists of the family directors of the mentioned organizations. The empiric stage allowed for showing evidence of how the succession andprofessionalization processes have been conducted in the researched companies. The analysis of the succession processes show the deep symbiosis of many aspects, such as family and personal relationships, political and symbolic, among others, that condition and orient the succession. The discussion about the professionalization process has evidenced, among other aspects, that this process has not eliminated the family-like character of management. The empirical plan also contemplated the analysis of societary issues, making clear the main challenges that arise from the evolution of property and growth of family owned businesses. As far as the structuring of governance in the family owned business, it was possible to understand this question under thescope of power relationships, discussing its formalization level starting from tacit directives, and based on idiosyncratic factors that are present on all researched organizations. In synthesis, it was verified that the construction of governance in family owned businesses must be understood as a process through which the consensus between the involved actors can be established considering family values, tradition and the power historically concentrated on the mangers of these organizations.